THE IMPACT OF GENERAL AND ORAL HEALTH STATUS ON REMOVABLE DENTURES AND QUALITY OF LIFE AMONG THE ELDERLY. A LITERATURE REVIEW - Mădălina Bicheru; Cristina Teodora Preoteasa; Marina Imre; Elena Preoteasa (Amaltea Medical Publishing House, 2018)
Given the recent demographic trends toward a marked increase of the elderly populations - as evidenced globally and also in Romania, an awareness regarding the specific needs of this age group is required regarding both the general health and the prosthodontic treatment. Method. A literature review of studies published after the year 2000 was performed, regarding the association between general and oral health among the elderly, as well as the association with the prosthodontic treatment and quality of life. Results and discussion. Specific elderly groups were first defined: young elderly (60-69 y.o.), middle-aged elderly (70-79 y.o.), and oldest elderly (over 80 y.o.) in order to provide a more clear picture of the transformations occurring among elderly patients. Multiple morbidities and multiple prescription drugs are often associated to oral health symptoms (e.g., the "dry mouth" or "burning mouth" syndromes), to general conditions such as frailty, disability, cognitive impairment, and also to more severe oral health diagnoses. Among the elderly, there is a strong correlation between the general and oral health, such as the one between periodontal disease and systemic inflammatory processes - which are moderated by age and socio-economic status. Thus, edentulation and removable dentures (conventional or implant-sustained) have an impact not only upon oral but also upon systemic health, as well as the overall quality of life. Conclusions. Given the recent trends toward an increase of the elderly populations, a systemic perspective is absolutely necessary for approaching a prosthetic treatment. The type and quality of dentures, as well as their acceptance by the elderly patient are closely related to the overall and oral health, the social-economic status, and the quality of life of the elderly patient.